Strategy Of Islamic Religious Education Teachers Towards The Development Of Self-Confidence Of Students Of SMA N 2 Kroya Cilacap - Rachmawati, Jeni; Imron, Ali; Khoiri, Ahmad (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
Self-confidence is an attitude or belief in one's own abilities that makes someone not easily anxious, free to do things according to their wishes, and responsible for the actions taken. In addition, confident people are also polite in interacting with others, have the motivation to achieve, and can recognize their strengths and weaknesses. In completing this research, the author used a descriptive qualitative research method. The results of the study showed that: the concept of Islamic religious education teachers in developing students' self-confidence is the recognition of self-potential, critical thinking and daring to express opinions, and the ability to take roles both in and outside the classroom. The strategies of Islamic religious education teachers towards developing students' self-confidence include six strategies, namely humanistic learning strategies, participatory learning strategies (Active Learning), experience-based learning strategies (Experiential Learning), motivation and appreciation-based learning strategies, integrative strategies with digital media, and self-actualization activities as part of the strategy. The success factors of Islamic religious education teacher strategies in developing students' self-confidence are teacher consistency in implementing strategies, periodic strategy evaluations, cooperation between Islamic religious education teachers, homeroom teachers, and BK teachers, support from the school, and the availability of space for self-actualization through religious activities.